2019
DOI: 10.1016/j.ijmultiphaseflow.2018.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Microlayer formation and depletion beneath growing steam bubbles

Abstract: Microlayers, the few-microns-thick layers of liquid that sometimes remain beneath bubbles growing on a heated substrate, are widely observed in experiments, but theoretical understanding of their formation, behaviour and role in bubble growth is limited. In this paper we present detailed interface-tracking simulations of the formation and depletion of such microlayers. Validation of our results is presented to the degree that available measurements of such a rapid and microscopic phenomenon allow. The work ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 35 publications
2
18
0
Order By: Relevance
“…Another important area of active research is focussed on the evaporation process as it happens near the solid surface. Two evaporation mechanisms have been so far identified, one taking place at the solid-vapour-liquid contact line [65] and involving the effect of molecular interactions between the solid substrate and the evaporating vapour-liquid interface, and one in which a liquid microlayer [66][67][68] of a few microns in thickness is observed to form and subsequently deplete due to evaporation on the heated surface. These are still poorly understood phenomena currently being investigated from a fundamental perspective.…”
Section: Modelling Bubble-wall Interactionmentioning
confidence: 99%
See 3 more Smart Citations
“…Another important area of active research is focussed on the evaporation process as it happens near the solid surface. Two evaporation mechanisms have been so far identified, one taking place at the solid-vapour-liquid contact line [65] and involving the effect of molecular interactions between the solid substrate and the evaporating vapour-liquid interface, and one in which a liquid microlayer [66][67][68] of a few microns in thickness is observed to form and subsequently deplete due to evaporation on the heated surface. These are still poorly understood phenomena currently being investigated from a fundamental perspective.…”
Section: Modelling Bubble-wall Interactionmentioning
confidence: 99%
“…Extension to the more challenging flow boiling conditions is at present outside the remit of current modelling techniques. Nevertheless, recently reported applications [67,69] enabled gaining unprecedented insight on the hydrodynamics and heat transfer of bubble behaviour in boiling.…”
Section: Application Of Interface-capturing Simulationmentioning
confidence: 99%
See 2 more Smart Citations
“…published works [45,46,19] where it is demonstrated that the microlayer formation and depletion are dynamic phenomena affecting the first part of the bubble growth only. Therefore, the existence of a micro-layer in the present configuration could maybe affect the tran-sitory behaviour of the bubble, but the micro-layer will be anyway depleted before a stationary equilibrium is reached.…”
Section: Numerical Simulation Of a Bubble Nucleated In Zero Gravity Cmentioning
confidence: 99%